Qualitative study exploring barriers and facilitators to progression for female medical clinical academics: interviews with female associate professors and professors. Issue 3 (14th March 2022) - Trusson, Diane; Rowley, Emma
Abstract : Objectives: This study aimed to explore the barriers and facilitators to career progression for female medical clinical academics from the perspectives of female associate professors and professors, with a particular focus on women with caring responsibilities. Design: An exploratory qualitative approach was adopted. Data from semistructured interviews conducted via video calls were analysed using thematic analysis. Setting: Two major universities in the East Midlands of England. Participants: The sample consisted of 13 female medical clinical academic associate professors and professors representing a range of medical specialties. Results: Female medical clinical academics experienced barriers and facilitators to progress at individual, interpersonal, institutional/procedural and societal levels. Conclusions: Many barriers experienced at an individual level by female medical clinical academics are heavily influenced by their interpersonal relationships, the academic environment in which they work and broader institutional and procedural issues which, in turn, are influenced by stereotypical societal views on gender roles. Facilitating factors, including measures to increase the numbers of female leaders, may lead to a change of culture that is supportive to aspiring female clinical academics as well as enabling a healthy work/life balance for women and men with caring responsibilities.